Regulation dynamics of exploited and protected populations of Haliotis roei, and their response to a marine heatwave. (20th July 2018) - Hart, Anthony M; Strain, Lachlan W S; Brown, Jamin
Abstract: Exploited and protected populations of Haliotis roei in Western Australia were significantly perturbed by a marine heatwave of 2010/11. The immediate effects were a decline in large animals and recruitment, followed by a lagged decline in the spawning biomass. The data describing these effects were fitted to models of the population dynamic transitions. Depensatory density dependence in recruitment is offset by compensatory density dependence in during replacement and together they create the population equilibrium points. Equilibrium densities were highly influenced by the environmental perturbation, with observed patterns suggesting a temporary 'regime shift' had occurred. The main implication for management is to maximise spawning biomass as recruitment is positively correlated with it with some evidence of an Allee effect at low spawning densities, but no evidence of compensatory density dependence at high densities. Development of forecasting models that utilised pre-recruit densities, adjusted for density-dependent replacement, and incorporated an environmental effect, assisted early-management intervention to stock declines. Such an approach is an alternative to traditional assessments which recommend using biological reference points that assume population regulation occurs in the recruitment transition. This assumption cannot easily explain why the high density unfished stock showed the least resilience to the environmental perturbation.